HABERMAS, J. (2022). Refugiados, migrantes e integración. Una breve antología. Ed. Juan Carlos Velasco. Madrid: Tecnos. - Fernández-Jardón, Francisco (Daimon Revista Internacional de Filosofia, 2022)
Reseña de: HABERMAS, J. (2022). Refugiados, migrantes e integración. Una breve antología. Ed. Juan Carlos Velasco. Madrid: Tecnos.